A Randomised Comparative Clinical Study to Evaluate the Efficacy of Aragwadhadi Kashaya Prakshalana Followed by Swarjikadhya Taila Pichu and Jatyadi Taila Pichu Application in The Management of Dushta Vrana W.S.R. to Non-Healing Ulcers (AYUSHDHARA, 2024)
Dushta Vrana is a type of Vrana which presents with delayed healing. The management of Dushta Vrana has been described in various Ayurvedic texts. Many formulations are in use for centuries out of those formulations. Present Study is to manage it with Shodhana Kashaya and Ropana Taila and treat Dushta Vrana. Aims and Objectives: 1. To evaluate the efficacy of Aragwadhadi Kashaya Prakshalana followed by Swarjikadhya Taila application in the management of Dushta Vrana. 2. To evaluate the efficacy of Aragwadhadi Kashaya Prakshalana followed by Jatyadi Taila application in the management of Dushta Vrana. 3. To compare the efficacy of both the groups in the management of Dushta Vrana. Methodology: It is a comparative clinical study with pre-test and post-test design where in 60 patients diagnosed with Dushta Vrana of either sex was randomly assigned into two groups of 30 members each in Group A and Group B. Intervention: Group A: Aragwadhadi Kashaya Prakshalana followed by Swarjikadhya Taila Pichu for 30 days. Group B: Aragwadhadi Kashaya Prakshalana followed by Jatyadi Taila Pichu for 30 days. Observations and Results: The effect of the treatment in both the groups were assessed by applying Wilcoxon rank sum test within the groups and Mann-Whitney U test between the groups, it showed that Group B is slightly better than Group A but both the groups showed equally good results. Discussion and Conclusion: It can be concluded from the study that in the management of Dushta Vrana - Aragwadhadi Kashaya Prakshalana followed by Swarjikadhya Taila Picchu and Jatyadi Taila Picchu Chikitsa both the drugs were highly effective in wound healing.